Preoperative Inflammatory Markers as a Predictor of Three-Year Overall Survival in Older Cancer Patients Undergoing Oncologic Surgery - Brattinga, Baukje (Cancers (Basel), 2021)
SIMPLE SUMMARY: Older patients can have an increased expression of inflammatory cytokines due to ageing of the immune system. It is likely that older cancer patients with a low-grade inflammatory state are more at risk for an exaggerated inflammatory response to surgery and for poor outcome after surgery. The aim of this study was to examine whether preoperative inflammatory markers could be a predictor of overall survival in older patients undergoing oncologic surgery. In this prospective cohort study, a plasma level of C-reactive protein (CRP) ≥ 10 mg/L was a predictor of inferior three-year overall survival after oncologic surgery in older cancer patients, and also for the specific group of older patients with a colorectal tumor. Measuring preoperative plasma level of CRP might be useful in risk stratification for poor outcome after surgery in older cancer patients. ABSTRACT: Oncologic surgery results in substantially higher morbidity and mortality rates in older patients compared to younger patients, yet little is known about the relation between the preoperative inflammatory state and postoperative outcome in the specific group of older cancer patients. The aim of this study was to examine whether preoperative inflammatory markers could be a predictor of overall survival in older patients undergoing elective surgery for a solid malignant tumor. Patients 65 years and older undergoing surgery for a solid malignant tumor were included in a prospective cohort study. Inflammatory markers C-reactive protein (CRP), interleukin-1 beta (IL-1β), IL-6, IL10, IL-12 and tumor necrosis factor-alpha (TNF-α) were measured in plasma samples preoperatively. The main outcome was overall survival three years after surgery. Between 2010 and 2016, 328 patients with a median age of 71.5 years (range 65–89) were included. A significantly higher mortality rate three years after surgery, was found in patients with high preoperative plasma levels of CRP and IL-6 (p = 0.013 and p = 0.046, respectively). In multivariate analysis, corrected for variables such as age, disease stage, frailty, comorbidities, type of surgery and complications, a preoperative plasma level of CRP ≥ 10 mg/L was an independent prognostic factor for inferior overall survival three years after surgery (multivariate hazard ratio 1.50, 95% confidence interval 1.04–2.16, p = 0.031). Also, for the specific group of patients with colorectal cancer, a preoperative plasma level of CRP ≥ 10 mg/L was a prognostic factor for inferior survival three years after surgery (multivariate hazard ratio 2.40, 95% confidence interval 1.20–4.81, p = 0.014). Preoperative elevated plasma level of CRP is an independent unfavorable prognostic factor for overall survival three years after oncologic surgery. This gives more insight into the relationship between inflammation and survival in older cancer patients, and might contribute to risk stratification for poor outcome after surgery in older cancer patients.